A Study on Parents Attitude Towards Information Technology (IT) Usage by Children - Magar, Deena (Shahid Kirti Multidisciplinary Journal, 2024)
This study explores about the parent’s attitude towards information technology usage by children. This qualitative study follows explorative research design which is based on narratives of 13 parents from Madhyapur, Thimi-Bhaktapur who were selected through purposive sampling. Narratives from in-depth interview with parents are used as data collection tools in the study. Social constructivism, attachment theory and other literature reviews are used to explore the research questions and strengthen the findings of study. Thematic analysis of parent narratives supports to achieve research objectives. This study shows that, majority of parents have positive attitudes towards their children’s usage of information technology in term of education, communication skills rather than risks associated with it. Study found main factors that can mold children’s technology usage are parent-child relationship, family educational and economic background, parenting styles, child’s age, gender and experience.